2016
DOI: 10.1080/14702541.2016.1157203
|View full text |Cite
|
Sign up to set email alerts
|

Trimline Trauma: The Wider Implications of a Paradigm Shift in Recognising and Interpreting Glacial Limits

Abstract: Trimlines mark the boundary between glacially eroded landscapes on low ground and landscapes dominated by evidence of periglacial weathering on higher summits. For many years the trimlines of Scandinavia, Britain and Ireland have been interpreted as marking the surface of the ice sheets at the maximum of the last glaciation, but recent cosmogenic exposure dating of erratics far above the trimlines in NW Scotland shows this to be false. The trimlines in that area must represent an englacial thermal boundary bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…100 m total uplift based on reports of former shoreline displacement or modelling attempts seems reasonable (Svendsen and Mangerud, 1987;Fjeldskaar et al, 2000;Steffen and Wu, 2011). For Blåhø, the total postglacial uplift is estimated at around 300 m (Morén and Påsse, 2001). However, this postglacial uplift cannot be described as a linear function as data from other localities in western Norway highlight (e.g.…”
Section: Exposure Age Calculationsmentioning
confidence: 91%
“…100 m total uplift based on reports of former shoreline displacement or modelling attempts seems reasonable (Svendsen and Mangerud, 1987;Fjeldskaar et al, 2000;Steffen and Wu, 2011). For Blåhø, the total postglacial uplift is estimated at around 300 m (Morén and Påsse, 2001). However, this postglacial uplift cannot be described as a linear function as data from other localities in western Norway highlight (e.g.…”
Section: Exposure Age Calculationsmentioning
confidence: 91%
“…The use of trimlines to constrain ice sheet thickness is not unique to Ireland or the Irish component of the BIIS and although their reinterpretation as englacial features may not be universally applicable, a re‐assessment of traditional views on ice sheet extent and thickness is required (McCarroll, ). For example, Lloyd et al .…”
Section: Discussionmentioning
confidence: 96%
“…The use of trimlines to constrain ice sheet thickness is not unique to Ireland or the Irish component of the BIIS and although their reinterpretation as englacial features may not be universally applicable, a re-assessment of traditional views on ice sheet extent and thickness is required (McCarroll, 2016). For example, Lloyd et al (2013) note that thicker Scottish ice could potentially resolve the apparent misfits between field and modelled Lateglacial RSL data from Cumbria, north-east England.…”
Section: Implications For Existing Gia Modelsmentioning
confidence: 99%
“…An early challenge to this view came from Trotter (1929a), who suggested that the blockfield had survived beneath thin and passive glacier ice; indeed it is now more conventional to interpret the transition between upper drift limits and blockfield as thermal boundaries in ice sheets (e.g. Phillips et al, 2006;Kleman and Glasser, 2007;Ballantyne, 2013;McCarroll, 2016).…”
Section: Previous Investigationsmentioning
confidence: 99%
“…Figure 1). The alternative interpretation of these proposed palaeonunataks as being areas that were ice covered but lying above the transition zone between high altitude cold based and lower altitude warm-based ice is now more widely preferred (Trotter, 1929a;Phillips et al, 2006;Kleman and Glasser, 2007;Ballantyne, 2013;McCarroll, 2016).…”
Section: Descriptionmentioning
confidence: 99%